Raden Mas - Krishnan L ([S.l.] : Cathay-Keris Film [production company] ; Kuala Lumpur : Grand Brialliance [distributor])
Sebuah filem melayu klasik
Copy available in DVD format
Penyunting, George Peterson, Ng Cheng Liat ; pengarah fotografi, Tsin Ming Chin
Latiffah Omar, Siput Sarawak, M. Amin, Noordin Ahmad
Keywords: Motion pictures -- Malaysia; Love in motion pictures; Malay drama